Incidence of Dysphagia after Acute Stroke - Sidra Ansar, Muhammad Ahmed, Saira Zaman, Rabia Azmat, Azam Khan, Athar Adnan Uppal, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: It has been reported that dysphagia is a commonly documented morbidity after stroke, but its reported frequencies are widely discrepant. There is emerging evidence that early detection of dysphagia in patients with acute stroke reduces not only these complications but also reduces length of hospital stay and overall healthcare expenditures. Aim: To determine the incidence of dysphagia after acute stroke. Methods: This is descriptive observational study was conducted between October 2013 to January 2014 at CMH Lahore.A total of 40 patients with stroke were included in this study.Incidence of dysphagia after acute stroke was determined by collecting data from the patients with stroke by using a questionnaire. The questionnaire constituted the questions regarding dysphagic issues. Results: Result indicated that out of 40 subjects 32(80%) were male and 8(20%) were female and the mean age of patients was 30.0± 88 years. The data on clinical findings of the patients with stroke showed that almost 27(67.5%) had swallowing problem and 13(32.5%) didn’t have swallowing problem. The evaluation of these patients with dysphagia showed that 3(7.5%) were diagnosed with swallowing problem at oral stage, 20(50%) at pharyngeal stage and 4(10%) at esophageal stage and level of their swallowing difficulty was 6(15%) mild, 10(25%) moderate and 11(27.5%) severe. Further investigation revealed that 10(25%) had coughing , 10(25%) choking and 7(17.5%) difficulty in swallowing and difficulty in swallowing reported by the patients was 14(35%) in liquids, 2(5%) in semi-solids and 11(27.5%) having problem in swallowing solids. Conclusion: It is concluded from the above study that incidence of dysphagia depends upon the severity of stroke and type of stroke. Keywords: Stroke, Dysphagia, Odonophagia.